The missing - Eidson, Thomas; Horner, James 1953-2015; Eidson, Thomas (Columbia Tristar Home Entertainment, 2004)
In 19th century New Mexico, a father comes home hoping to reconcile with his daughter, Maggie.Maggie is a young plainswoman raising her two daughters in the desolate wilderness of New Mexico. When daughter Lily is kidnapped by a dark-hooded phantom with shape-shifting powers, Maggie's long-estranged father offers to help find her. Though stunned by his return, Maggie knows she must swallow both hurt and pride if she is ever to see Lily again. Unaware of the frightening events that lurk in the distance, father and daughter set out to track down the fiend that took Lily. But lying in wait is horror so unspeakable it will change them all forever
Bildformat 2.40:1 (16:9 widescreen)
Orig.: USA 2003
Enth. entfallene Szenen ; outtakes ; alternatives Filmende (2 Versionen) ; Ron Howard erzählt von ... ; Ron Howards frühe Werke ; Fotogalerie
Keywords: Fathers and daughters -- Drama; Kidnapping victims -- Drama; Shapeshifting -- Drama; Feature films; Fiction films; Horror films; Video recordings for the hearing impaired